Business continuity and disaster recovery – advice for best practice. Issue 11 (November 2018) - Timms, Paul
Abstract : With downtime leading to reputational damage, lost trade and impact on long-term projects, organisations are starting to realise that continuity planning and disaster recovery are critical to success. Business continuity needs to be properly planned, tested and reviewed in order to be successful. For most businesses, planning for disaster recovery will raise more questions than answers to begin with: however by ensuring you do the hard work now you will save a lot of pain in the future.